2022
DOI: 10.3390/cryst12050656
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprints of Topotactic Hydrogen in Nickelate Superconductors

Abstract: Superconductivity has entered the nickel age marked by enormous experimental and theoretical efforts. Notwithstanding, synthesizing nickelate superconductors remains extremely challenging, not least due to incomplete oxygen reduction and topotactic hydrogen. Here, we present density-functional theory calculations for nickelate superconductors with additional topotactic hydrogen or oxygen, namely La1−xSrxNiO2Hδ and LaNiO2+δ. We identify a phonon mode as a possible indication for topotactic hydrogen and discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…As a result, decomposition has been observed in reduced infinite-layer thin films 37,[71][72][73] ; the precise identification of the decomposition products is, however, difficult in thin films in part due to the small film volume. An additional challenge associated with metal hydride reductions is the possibility of hydrogen incorporation in the lattice, an effect which has been proposed as a reason for the absence of superconductivity in some films 70,74,75 promising alternative to metal hydride reductions 76 . Thus to minimize the formation of decomposition products and potential hydrogen intercalation during metal hydride reductions, careful optimization of reduction duration and temperature is essential.…”
Section: Mbe Synthesis Of Ruddlesden-popper Nickelatesmentioning
confidence: 99%
“…As a result, decomposition has been observed in reduced infinite-layer thin films 37,[71][72][73] ; the precise identification of the decomposition products is, however, difficult in thin films in part due to the small film volume. An additional challenge associated with metal hydride reductions is the possibility of hydrogen incorporation in the lattice, an effect which has been proposed as a reason for the absence of superconductivity in some films 70,74,75 promising alternative to metal hydride reductions 76 . Thus to minimize the formation of decomposition products and potential hydrogen intercalation during metal hydride reductions, careful optimization of reduction duration and temperature is essential.…”
Section: Mbe Synthesis Of Ruddlesden-popper Nickelatesmentioning
confidence: 99%
“…The subsequent reduction for NENO is achieved by in situ reduction using an Al capping method described in ( 8 ). The reduction method minimizes hydrogen intercalation effects ( 15 , 16 ). The schematic reaction diagram is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some recent work in currently archived and preprint articles implies that issues with structural defectsincluding layer bucklingcould be inhibiting superconductivity. , Another prevailing hypothesis is that hydrogen incorporation as a byproduct of the hydride reduction technique affects the electronic properties and, therefore, the presence or absence of superconductivity. Some computational studies and experimental data imply that hydrogen incorporation may be necessary for superconductivity, while some show that this incorporation leads to decreased conductivity. SIMS experiments on superconducting nickelates further give contradictory results regarding the significance of hydrogen in these systems. , Neutron diffraction studies have indicated that there is not a significant amount of hydrogen incorporation in bulk LaNiO 2 powder but have not quantified the upper limit of hydrogen present. The presence of strain in thin films could explain the difference in properties between bulk and film samples as well as any differences in the propensity for hydrogen incorporation.…”
Section: Introductionmentioning
confidence: 99%